2021
DOI: 10.6004/jnccn.2021.0042
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia, Version 2.2021, NCCN Clinical Practice Guidelines in Oncology

Abstract: The NCCN Guidelines for Acute Lymphoblastic Leukemia (ALL) focus on the classification of ALL subtypes based on immunophenotype and cytogenetic/molecular markers; risk assessment and stratification for risk-adapted therapy; treatment strategies for Philadelphia chromosome (Ph)-positive and Ph-negative ALL for both adolescent and young adult and adult patients; and supportive care considerations. Given the complexity of ALL treatment regimens and the required supportive care measures, the NCCN ALL Panel recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 223 publications
(353 reference statements)
0
104
0
4
Order By: Relevance
“…In the setting of adult patients, two retrospective studies from Sasaki et al, including one propensity score analysis, suggested superiority of ponatinib + HCVAD over imatinib or dasatinib + HCVAD [ 167 , 168 ]. However, there is to date no prospective available data that compares different TKIs for adult Ph+ ALL patients and no specific guidelines [ 109 ]. Prospective randomized trials are currently ongoing ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the setting of adult patients, two retrospective studies from Sasaki et al, including one propensity score analysis, suggested superiority of ponatinib + HCVAD over imatinib or dasatinib + HCVAD [ 167 , 168 ]. However, there is to date no prospective available data that compares different TKIs for adult Ph+ ALL patients and no specific guidelines [ 109 ]. Prospective randomized trials are currently ongoing ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Allo-HSCT is still standard of care for eligible patients in CR1 [ 109 ]. However, its role has become less clear with the advent of 2G/3G-TKIs with lower allo-HSCT rates in these trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Response assessments were performed according to the NCCN guidelines for acute lymphoblastic leukemia (version 2. 2021) [ 9 ]. Event-free survival (EFS) was defined as the time from complete remission (CR) after the VPD regimen until relapse, death, or last follow-up date, whichever occurred first.…”
mentioning
confidence: 99%